Editorial - Madan Bhandari Memorial College (Journal of Productive Discourse, 2025)
As we present this issue of the Journal of Productive Discourse, we reflect on the intellectual and political legacy of one of Nepal’s most influential statesmen—Nepal Ratna and People’s Leader, Madan Bhandari. Born on 27 June 1952 in Dhungesanghu, Taplejung, Bhandari began his formal education in a local Sanskrit pathshala. He later pursued higher education in Varanasi, India, completing his undergraduate degree in Sanskrit Literature and studying postgraduate courses in Oriental Philosophy at Banaras Hindu University. During this formative period, Bhandari became politically active and subsequently joined the Communist Party of Nepal as a full-time cadre under the leadership of Comrade Pushpa Lal Shrestha. Bhandari’s ascent within Nepal’s leftist political sphere culminated in his instrumental role during the 1990 People’s Movement, a landmark event that led to the restoration of multiparty democracy in the country. His theoretical contribution, most notably the principle of People’s Multiparty Democracy, has had a profound and enduring impact on Nepal’s political trajectory, shaping both the ideological orientation and institutional structures of the post-1990 democratic era (Dhakal, 2023). Such a magnanimous statesman was killed in a mysterious road accident in Dashdhunga of Chitwan district on Jestha 3, 2050 B.S. (May 16, 1993). To commemorate his mission of serving people and the nation, the Journal of Productive Discourse is published every year on his soulful Memorial Day. This issue of the Journal of Productive Discourse presents a diverse and interdisciplinary collection of scholarly articles addressing a broad spectrum of contemporary themes, including alternative media, the lived experiences of unemployed individuals, poverty, artificial intelligence, public health, knowledge management practices, organizational ethics in the education sector, consumerism, development discourse, literature, and social entrepreneurship. These contributions align closely with the vision and mission of the Journal of Productive Discourse: to advance innovative scholarship, interrogate prevailing paradigms, and foster forward-thinking perspectives across academic and professional domains. Particularly, three articles in this issue exemplify this commitment. A notable contribution by Dura examines the diverse theoretical frameworks and conceptualizations of alternative media, tracing their evolution from traditional forms to contemporary digital platforms. The study highlights the dynamic nature of alternative media in the digital age, where decentralized platforms challenge dominant narratives and create new avenues for grassroot communication (Dura, 2025). Another important study by Agrawal explores the relationship between perceived ethical climate and faculty commitment in private higher secondary schools in Kathmandu and Lalitpur. The findings reveal significant correlations between three types of ethical climates—egoistic, benevolent, and principled—and faculty commitment. Among them, the benevolent climate exerts the most positive influence, while the egoistic climate is associated only with continuance commitment (Agrawal, 2025). Similarly, the study by Gautam investigates awareness, perceptions, and implementation of knowledge management practices in community colleges within the Kathmandu Valley. Focusing on knowledge acquisition, organization, and application, the research provides practical recommendations for policymakers and academic institutions to develop structured frameworks that foster a knowledge-driven culture in Nepalese higher education (Gautam, 2025). As editors, we are especially encouraged by the increasing participation of faculties and students in research initiatives, which reinforces our QAA-certified college’s efforts to strengthen its research culture in alignment with emerging pedagogical approaches. Such engagement is critical for cultivating a sustained ethos of inquiry and innovation in the institution. We trust that this collection will serve the interests of our readers, encouraging critical thinking, promoting dialogue, and inviting collaborative exploration among scholars and practitioners alike. We welcome constructive feedback and reflections that can help us grow through rigorous, rational discourse. Finally, we extend our sincere appreciation to all stakeholders, including the College Management Committee, academic staff, students, and researchers, for their valuable contributions and continued support. Editorial Board May 2025